2001
DOI: 10.1053/jhep.2001.22168
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids induce eosinophil degranulation by two different mechanisms

Abstract: Eosinophil infiltration and activation occur in the vicinity of the bile ducts in immune cholangiopathies. When cholangiocytes are injured, bile acids may cross the damaged biliary epithelia and affect periductal immune cells. Although immunomodulatory actions of bile acids have been well explored, their effects on eosinophils have never been examined. In this study, we tested the hypothesis that bile acids directly activate eosinophils and induce their effector functions. We found that a hydrophobic bile acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Furthermore, BAs inhibit the lipopolysaccharide (LPS)‐induced expression of the proinflammatory cytokines TNF‐α and IL‐6 in primary human macrophages . In contrast, it has been found that treatment of eosinophils with TCDCA and TUDCA induced the production of high amounts of IL‐8 . Thus, the functional influence of BAs on the immune system may vary depending on different immune cell types and conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, BAs inhibit the lipopolysaccharide (LPS)‐induced expression of the proinflammatory cytokines TNF‐α and IL‐6 in primary human macrophages . In contrast, it has been found that treatment of eosinophils with TCDCA and TUDCA induced the production of high amounts of IL‐8 . Thus, the functional influence of BAs on the immune system may vary depending on different immune cell types and conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A minor fraction of BAs escapes the enterohepatic circulation and reaches the systemic circulation where they regulate many processes, including lipid and glucose homeostasis, intestinal motility, inflammation and configuration and growth of the gut microbiome . A direct impact of BAs on the function of innate immune cells such as monocytes, macrophages and granulocytes has been reported .…”
Section: Introductionmentioning
confidence: 99%
“…Previously we have demonstrated that solar radiation can rapidly induce sporozoite de-granulation, significantly affecting the ability of sporozoites to successfully attach and infect a compatible host cell (King et al 2010). Interestingly, bile salts have previously been demonstrated to induce de-granulation (relating to secretion and exocytosis) in a range of mammalian cells (Hardcastle et al 2001; Yamazaki et al 2001). This work provides the first evidence that bile, and in particular a bile salt, can directly affect intracellular calcium signalling in an Apicomplexan, and to our knowledge provides only the second report of an external host signal associated with affecting intracellular calcium signalling and controlled secretion of apical organelles (Singh et al 2010).…”
Section: Discussionmentioning
confidence: 99%